Experimental Investigation of CNT Coated Tools for EDM Processes. (2018) - Shirguppikar, S.S.; Patil, M.S.; Ganachari, V.S.; Kolekar, T.V.; Jadhav, P.S.; Chougule, A.B.
Abstract: In EDM process while machine operated on high current and pulse on time values it leads to increase tool wear rate. The aim of this research work was to create a methodology to minimize the tool wear rate at high values of energy related parameters in EDM. The experimental work is investigated comparative study with coated tool electrode and with non coated tool electrode. Copper electrodes are used as tool electrode then it coated with carbon nano tubes for further experimental work. Design of experiment (DOE) is done with Taguchi method and results discussed with ANOVA. The machining results showed that the tool wear rate (TWR) decreases and material removal rate (MRR) increases with coating of CNT on copper electrodes.